Analisis Dan Pemilihan Strategi Umum Yang Digunakan Para Pedagang Kaki Lima Di Kawasan Pantai Padang - Susriyanti, Susriyanti; Yeni, Fitri; Wijaya3, Roni Andri; Diana, Yusvi (Jurnal Pengabdian Masyarakat Akademisi, 2025)
This community service activity was carried out for traders in the Padang Beach area. This service carries the title "Analysis and Selection of General Strategies Used by Street Vendors in the Padang Beach Area". Strategy is a pattern of activities that seeks ways or tips for every business actor or trader in marketing what they sell. Choosing the right strategy will determine the pattern and victory that will be obtained in the existing business competition arena. This activity aims to observe and analyze which general strategies have been used by street vendors in the Padang Beach area so far. The activity was carried out directly through surveys, observations, interviews, question and answer interactions in focus group discussions by dividing the team into 6 groups. From the results of questions and answers, interviews, and discussions, it is known that almost all general strategies in strategic management have been carried out, such as focus strategies and low-cost strategies. However, for differentiation strategies, there are still very few because the majority of what they trade is almost the same. Coupled with the limited capital resources, it is increasingly difficult for them to create differentiation.